Silabus & Rencana Pelaksanaan Pembelajaran Bahasa Indonesia - Main Sufanti; Joko Santoso; Nuraini Fatimah; Dini Restiyanti Pratiwi (Muhammadiyah University Press, 2017)
xxiv + 328 hlm ; illust ; 15,5 x 23 cm